Analisis Penyebab Kesulitan Berhitung Pada Anak Usia 5-6 Tahun - Yuliasti, Tatia; Vitaloka, Wulansari (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
Difficulty counting in children aged 5-6 years is a challenge in cognitive development that can have an impact in their academic readiness. This research aims to analyze the factors that cause difficulties in counting among children in Pendung hilir Village, Air Hangat District, Kerinci Regency. This research uses a qualitative method with a descriptive approach. The research subjects consisted of five children who had difficulty counting, while the informats were their parents. Data Was collected through observation, interviews and documentation. The research results dhow that children’s numeracy difficulties are caused by four main factors. First, lack of practice in counting. Second, dependence on cell phones reduces children’s focus and motivation to learn. Third, children’s lack of interest in learning to count. Fourth, children’s learning styles are not given enough attention. This research confirms that to improve children’s numeracy skills, more interactive learning strategies are needed, such as educational games, visual aids, as well as active involvement of parents in guiding children. Eith a more appropriate approach, it is hoped that children will be better prepared to face the next level of education and have a better understanding of the concept of numbers.